Analysis of Lipid Metabolism and Transcriptome Differences Before and After Wax Loading in Wax Gourd - Jinqiang YAN; Zhenqiang CAO; Jiesheng HONG; Piaoyun SUN; Wenrui LIU; Dasen XIE; Biao JIANG (Guangdong nongye kexue, 2025)
【Objective】To explore composition and regulatory mechanism of the wax powder on the fruit surface of wax gourd, lipid metabolism and transcriptome was performed to analyze lipid and gene expression differences before and after wax loading.【Method】Wax gourd inbred line 'P131' was used as plant material and its fruit peel was cut and collected at 10 and 20 days after pollination. UPLC-MS/MS was applied to analyze the lipid composition and differences between these two stages. Transcriptome analysis was performed to understand differentially expressed genes between them. Moreover, KEGG and GO enrichment was done to understand main biological pathways involved during this period.【Result】In total, 267 lipids were identified in the fruit peel of 'P131' at 10 and 20 days after pollination, and 85 lipids were found differentially accumulated between these two stages. Among these lipids, the contents of DGDG18:3_20:3, MGDG18:3_20:3 and PI16:0_18:1 were significantly higher in the fruit peel at 20 days after pollination than that at 10 days after pollination. Totally, 343 genes were found differentially expressed in the fruit peel of wax gourd inbred line 'P131' at 10 and 20 days after pollination, among which 120 were up-regulated while the other 223 were down-regulated based on transcriptome analysis, and CER1, TPS and other genes previously reported involved in wax formation were included. It was found that differentially expressed genes were enriched in KEGG pathways related with ester biosynthesis, such as 'Sesquiterpenoid and triterpenoid biosynthesis', 'Cutin, suberine and wax biosynthesis' and 'Biosynthesis of secondary metabolites'. GO enrichment analysis highlighted items related with lipid metabolism, includiung 'lipid metabolic process' and 'very long-chain fatty acid metabolic process'.【Conclusion】In conclusion, we preliminarily identified lipids and transcriptome differences during the wax loading period of wax gourd fruit. The results suggest that lipid metabolism and ester biosynthesis might relate with the process of wax powder formation.